Evaluation of land use density, diversity and ridership of rail based public transportation system - Mohamad Zulkifli, Siti Nur Awanis; Kadar Hamsa, Abdul Azeez; Hj. Mohd. Noor, Norzailawati; Ibrahim, Mansor (2016)
Objectives The evaluation of land use density, diversity and passenger ridership at LRT stations along Kelana Jaya and Ampang LRT line Data and methodology Data collection is one of the major parts of methodology. The main components of data include: land use density and diversity, public transportation system and passenger ridership. The data on land use will be collected by identifying transit stations along the existing Kelana Jaya and Ampang LRT lines. The selection of each station will be earmarked with a radius of 800 meters (the ideal walking distance of the pedestrians to and from the station) from the station for the collection of land use characteristics. Statistical correlation technique will be applied to evaluate the individual effects of land use density and passenger ridership. GIS mapping technique will be used to analyse the land use characteristics within the selected radius of the transit station. A statistical model will be developed to evaluate the combined effects of land use on the use of public transport. Expected results The results of the land use characteristics around the LRT stations for the rail-based public transport system are shown in this paper. Determination of LRT stations with different density, diversity and passenger ridership is highlighted in this paper.